The adequacy of tissue obtained by percutaneous needle autopsy in comparison to conventional autopsy for lung and liver tissues - Minnu Roy; Lekshmidevi P; Neetha Unnikrishnan; Sankar S (Asian Journal of Medical Sciences, 2024)
Background: Autopsies are done since the olden days to study anatomy, to learn pathology, and to identify the cause of death. However, this procedure is not widely accepted due to lack of facilities, reluctancies by relatives, various religious and ethical issues, and fear of transmission of communicable diseases. Percutaneous needle autopsies have bridged these shortcomings and provide better results when done under radiological guidance. Aims and Objectives: The aim of the study was to determine the adequacy of tissue obtained by percutaneous needle autopsy in comparison to conventional autopsy for lung and liver tissues. Materials and Methods: Descriptive study, done in autopsies performed in the Department of Forensic Medicine and Department of Pathology, Government Medical College Kottayam. Percutaneous needle samples are obtained from lungs and liver using surface landmarks. Samples are also obtained after opening the deceased body. After microscopic examination, adequacy is observed and morphological findings are compared. Results: In lungs, 164 samples met the adequacy criteria and 156 samples showed similar morphological findings by both methods; in the liver 159 samples met the adequacy criteria and 151 samples showed similar morphological findings by both methods. In lungs and liver, the most common histological finding was congestion. Conclusion: Percutaneous needle autopsies and the tissue thus obtained are adequate and comparable when compared to conventional autopsies. The findings are more comparable in diffuse lesions rather than in localized lesions.